The role of multi-agent in computational problem solving environments - Rajabi, Maryam; Mohd Aris, Teh Noranis (Elsevier B.V. (ScienceDirect), 2013)
Problem solving techniques is one of the earliest topics taught to novice students in computer programming course. In addition, novice students face difficulties in understanding problem statements and transforming them to problem solving techniques. Meanwhile, problem solving computing environments are not only powerful enough to solve complex problems but also are able to interact with human. Hence, the purpose of this paper is to investigate the designing of environments to assist novice programmers in computational problem solving using multi-agent technology and to develop a new visualization conceptual model.